Australian Melolonthini (Coleoptera: Scarabaeidae: Melolonthinae): a third species of Allothnonius Britton, 1978, and notes on the other known species - Allsopp, Peter G.; Smith, Andrew B.t. (Zootaxa, 2022)
The genus Allothnonius Britton, 1978 (Coleoptera: Scarabaeidae: Melolonthinae: Melolonthini) is revised based on material of the two previously described Queensland species, A. barretti Britton, 1978 and A. brooksi Britton, 1978; and A. mouldsi Allsopp & Smith, new species, from the northwest of the Northern Territory. The diagnostic characters of the genus are revised, distinguishing it from other Australian Melolonthini. The female of A. brooksi is described for the first time. An identification key, distribution map and notes on the natural history of the three species are included.